2008
DOI: 10.1007/s12103-008-9033-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Disadvantage and Family Violence: Neighborhood Effects on Attitudes about Intimate Partner Violence and Corporal Punishment

Abstract: Social disorganization theory asserts that neighborhood composition affects levels of violence within the community. The purpose of this article is to analyze the bivariate effects of social disorganization, crime, and collective efficacy, in addition to the individual factors of gender, race, and a history of child maltreatment, on the acceptance of using violence within the family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…A county’s median household income and whether a school receives Title I funding were also predictive of SCP use and amount of use, but to a lesser extent than the college education rate. These findings are consistent with research indicating higher acceptance and support for parental use of corporal punishment among people with lower levels of education and income (Button, 2008; Douglas, 2006). Overall, the similarity in associations of socioeconomic characteristics with both parental and school corporal punishment suggests that support for SCP and parental corporal punishment may stem from similar experiences and worldviews.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A county’s median household income and whether a school receives Title I funding were also predictive of SCP use and amount of use, but to a lesser extent than the college education rate. These findings are consistent with research indicating higher acceptance and support for parental use of corporal punishment among people with lower levels of education and income (Button, 2008; Douglas, 2006). Overall, the similarity in associations of socioeconomic characteristics with both parental and school corporal punishment suggests that support for SCP and parental corporal punishment may stem from similar experiences and worldviews.…”
Section: Discussionsupporting
confidence: 90%
“…Parents who are of low socioeconomic status express more positive attitudes toward parental corporal punishment (Button, 2008; Douglas, 2006). States where corporal punishment is legal, and where it is most prevalent, tend to have higher poverty and lower education rates than states where is it illegal or less widely used (Gershoff et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the CP factor was moderately correlated with both the CW and PV factors was interesting and relates to research indicating the association between harsh and physically punishing parenting approaches as a risk factor for youth aggression and violence (Button, 2008;Chaffin, 2006). Attitudes about violence related to crime and war were less related to partner violence attitudes among the current sample as observed by the small correlation between the CW and PV factors.…”
Section: Discussionsupporting
confidence: 64%
“…Relatedly, children who have parents with authoritarian attitudes regarding childrearing and who engage in harsh or inconsistent disciplinary practices are at greater risk for youth violence (Chaffin, 2006;DHHS, 2001). Furthermore, adults whose parents used corporal punishment on them as children have demonstrated increased supportive attitudes regarding aggression between intimate partners (Button, 2008). To wit, previous research has demonstrated physical discipline by parents to be predictive of aggressive behavior in children (Weiss, Dodge, Bates, & Pettit, 1992).…”
Section: Attitudes and Risk Factors Regarding Violencementioning
confidence: 99%
“…Strong values of privacy and noninterference in Indigenous communities may preclude intervention when violence occurs in intimate partnerships (Jones, ). As Button () wrote: “Violence that occurs behind closed doors may be reduced through the willingness of neighbors to uphold the common values of the community” (p.132). Research has shown that some Indigenous communities become more willing to discuss and respond to IPV as the magnitude of the problem increased, indicating positive social control (Hamby, ).…”
Section: Introductionmentioning
confidence: 99%